2019
DOI: 10.1111/apt.15187
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the NFkB, TNF‐alpha, IL‐1beta, and IL‐18 pathways are associated with response to anti‐TNF therapy in Danish patients with inflammatory bowel disease

Abstract: Summary Background Anti‐tumor necrosis factor‐α (TNF‐α) is used for the treatment of severe cases of IBD, including Crohn's disease (CD) and ulcerative colitis (UC). However, one‐third of the patients do not respond to the treatment. We have previously investigated whether single nucleotide polymorphisms (SNPs) in genes involved in inflammation were associated with response to anti‐TNF therapy among patients with CD or UC. Aim A new cohort of patients was established for replication of the previous findings an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 45 publications
4
54
0
Order By: Relevance
“…Although the association of the NFKB2 rs1056890 SNP with IL10 levels neither survive correction for multiple testing, our results were in agreement with previous studies demonstrating that NFKB2 unlikely NFKB1 is implicated in the control of antigen presenting cell function and not in the activation of T and B cells. Likewise, recent studies have also identified genetic polymorphisms within the NFKB pathway as genetic biomarkers for response to TNFi in RA 42 but also other autoimmune diseases 42 , which further supported our hypothesis suggesting a key role of the NFKB2 gene in modulating the response to TNFi. In addition, in silico tools such as Regulome showed that the rs1056890 SNP has a score of 4, which means that this polymorphism could affect transcription factor affinity and DNase peak 43 .…”
Section: Discussionsupporting
confidence: 87%
“…Although the association of the NFKB2 rs1056890 SNP with IL10 levels neither survive correction for multiple testing, our results were in agreement with previous studies demonstrating that NFKB2 unlikely NFKB1 is implicated in the control of antigen presenting cell function and not in the activation of T and B cells. Likewise, recent studies have also identified genetic polymorphisms within the NFKB pathway as genetic biomarkers for response to TNFi in RA 42 but also other autoimmune diseases 42 , which further supported our hypothesis suggesting a key role of the NFKB2 gene in modulating the response to TNFi. In addition, in silico tools such as Regulome showed that the rs1056890 SNP has a score of 4, which means that this polymorphism could affect transcription factor affinity and DNase peak 43 .…”
Section: Discussionsupporting
confidence: 87%
“…Almost all DEGs involved in the Toll-like signaling pathway were up-regulated, which was consistent with the recent study found that polymorphisms of TLR pathway are valuable significant predictors for the response to anti-TNFα therapy among patients with autoimmune disease. 50,51 Firstly, as motioned above, TLR pathway facility the production of lgG and thereby stimulate the FcγR signal. Secondly, FcγR stimulates phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…There are many logistic models that show the relationship between IBD varieties [26][27][28][29][30][31]. However, the most accurate model which could clearly point the appropriate group for the patient has not been found so far.…”
Section: Discussionmentioning
confidence: 99%